The Effect of Gonadotropin Releasing Hormone Administration on Fertility and Embryonic Loss in Goats during the Anoestrus Period - Köse, Ayşe Merve; Koldaş Ürer, Ece; Sarıbay, Mustafa Kemal; Doğruer, Gökhan; Karaka, Fikret; Çoskun Çetin, Nurdan; Demirezer, Haydar (Acta Scientiae Veterinariae, 2021)
Background: Following the induction of oestrus out of season in small ruminants, low fertility and variations in fertility rates are associated with embryonic losses. One of the main causes of embryonic loss is luteal dysfunction. Gonadotropin Releasing Hormone (GnRH) supports the luteal structure, and increasing progesterone levels may be beneficial in terms of promoting embryonic life. The main objective of the present study was to evaluate the efficacy of GnRH administration following an oestrus induction protocol in the anoestrus season for preventing embryonic loss in goats having failure to conceive during the season. Materials, Methods & Results: In the study, 106 Damascus goats aged 3-5 years and weighing 45-60 kg were used. The oestrus of 106 goats in the anoestrous group was stimulated with progesterone and pregnant mare serum gonadotropin (PMSG) treatment. Out of breeding season, goats were divided into the 4 following groups: GnRH0 (n = 27), GnRH7 (n = 26), GnRH0+7 (n = 27) and control (n = 26). In each goat, an intravaginal sponge (IS) containing 20 mg of fluorogestone acetate (FGA) was placed into the vagina and left for 9 days. With the withdrawal of the sponge, 550IU PMSG and 125 μg of d-cloprostenol were injected intramuscularly. Oestrus detection was made via teaser bucks for 3 days starting 24 h after withdrawal of the IS. Eighteen bucks known to be fertile were used for breeding. Goats in the oestrus period were mated via natural breeding. The GnRH analogue lecirelin was injected intramuscularly at breeding in the GnRH0 group, on day 7 post-breeding in the GnRH7 group, and both at breeding and on day 7 post-breeding in the GnRH0+7 group. No injections were given to the control group. Blood samples for progesterone measurement were taken by jugular vena puncturing on days 3, 6, 7, 10, 13, 16, and 19 after breeding from 10 randomly chosen goats in all groups. The goats with a level of > 3.5 ng/mL of progesterone on day 21 post-breeding were evaluated as pregnant. Pregnancy was also viewed on day 50 after breeding by real-time ultrasonography (USG) with a 5-7.5 MHz convex probe. The oestrus rate was 96.23% (102/106) in the goats. The rates of onset of oestrus between 36-48 h, 48-60 h and 60 h and beyond were 38.7% (41/106), 21.7% (23/106) and 35.8% (38/106), respectively. The total pregnancy rate was 35.8% (38/106). There were no statistically significant differences (P > 0.05) found for the pregnancy rate, embryonic death rate or progesterone concentration of the groups. However, serum progesterone levels were statistically different in the GnRH7 group compared with the control group (P < 0.05). Discussion: After synchronisation, various anti-luteolytic strategies can be used to support corpus luteum development and elevate progesterone concentration in the luteal phase to decrease embryonic loss and increase reproductive performance. Therefore, application of GnRH to support the luteal structure and to increase progesterone levels may be beneficial in terms of supporting embryonic life. The results showed that GnRH treatment on the day 7 post-breeding following oestrus induction, including FGA and PMSG, can increase serum progesterone levels in Damascus goats in the anoestrus period. However, following oestrus induction in the anoestrus period, it was seen that GnRH treatment at breeding or on day 7 after breeding did not have any positive effect on embryonic loss or reproductive performance. In conclusion, it was considered that this protocol could be implemented successfully, yielding a 35% pregnancy rate in Damascus goats in the anoestrus period, but embryonic loss must be deeply studied in detail.